PENGARUH PRESTASI PENDIDIKAN AGAMA ISLAM DAN INTENSITAS PENDIDIKAN AGAMA ISLAM DALAM KELUARGA TERHADAP AKHLAK SISWA SMA NEGERI 3 SALATIGA: Indonesia - Ahmad Hasan As'ari; Mustaghfiroh; Samsul Huda (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2021)
ABSTRACT This study aims to analyze the effect of Islamic Religious Education Achievement in Schools and the Intensity of Islamic Religious Education in Families Against Student Morals. This type of research is quantitative. This research was conducted at SMA Negeri 3 Salatiga. The population in this study included all students of SMA Negeri 3 Salatiga, totaling 1,101 students. As for the focus population is only limited to class XI, amounting to 365 students. The sampling technique was a random sampling of 55 students. Retrieval of data used is to use a questionnaire and documentation. The collected data were analyzed using multiple linear regression analysis with the help of SPSS program version 16.0. The results showed 1) the achievement of Islamic education in schools in the high category does not have a great effect on the morals of students with a significance level of 0.50%. 2) the intensity of Islamic religious education in families with good criteria has a significantly greater effect of 9.10%. 3) there is a positive and significant influence jointly the achievement of Islamic religious education in schools and the intensity of Islamic religious education in the family on the morals of students in class XI of Salatiga State High School 10.70% and the remaining 89.30% is influenced by other factors in outside this research variable. Keywords: Achievement, Family, Islamic and Moral Religious Education.